Reconsidering the Role of the Father as Qawwam in Family Resilience: A Study of Thematic Exegesis of the Qur'an - Dudung Abdul Karim; M Darwis Hude; Muhammad Hariyadi (ZAD Al-Mufassirin, 2026)
This study examines the reconsideration of the father's role in strengthening family resilience through a Qur'anic thematic exegesis (tafsir mawdhu'i) perspective, positioned as a proactive scholarly response to the growing phenomenon of fatherlessness in Indonesia. Employing a qualitative methodology integrating tafsir mawdhu'i with descriptive-analytical and socio-psychological hermeneutic approaches, this study systematically traces Qur'anic verses related to paternal roles across authoritative classical and contemporary tafsir works (including Tafsir al-Thabari, Ibn Kathir, Al-Kasysyaf, and Al-Tahrir wa al-Tanwir).  The findings reveal that the Qur'an constructs paternal responsibility as multidimensional: as accountable leader (qawwam) in An-Nisa'/4:34, just provider in Al-Baqarah/2:233, and moral-spiritual guardian through At-Tahrim/66:6.  Qur'anic paternal archetypes,Luqman (31:13–19), the Prophet Ya'qub (Yusuf/12:67–68), and Ibrahim,serve as comprehensive blueprints for active paternal involvement.  The novelty of this research lies in the formulation of a five-component integrated model: (1) paternal role optimization, (2) Islamic coping strategies, (3) ecoparenting, (4) Qur'an-based father–child relational development, and (5) father training programs, as a contextualized framework to prevent fatherlessness and strengthen family resilience in the Indonesian socio-cultural context.